Propaganda Expressions in “Angel and Demon” Novel by Dan Brown - Muh. Taufiq Syam (Sekolah Tinggi Agama Islam Negeri Majene, 2022)
This research studied about the kinds of propaganda expressions and what messages are conveyedthrough the propaganda expressions in Angel and Demon novel by Dan Brown. The research usedthe propaganda theory by Harold Laswell, that divided in four kinds; agitation, integration, horizontally and vertically propaganda. In the methodology of research, the writer used descriptive qualitativemethod and intrinsic and extrinsic approach. In this research, the writer found there are someexpressions that contain agitation propaganda, integration propaganda, horizontally propaganda andvertically propaganda that could be giving influence to the reader. In general, an expression ofpropaganda in “Angel and Demon” novel by Dan Brown wants to change the mindset of peopletowards their views to the brotherhood of the „Illuminati. The novel attempts to explain the history ofthe birth of a conflict between the Christian and the „Illuminati‟ and how much influence they hadbeen, the author packed them into a dialogue delivered by characters that are in the novel in whichthere are propaganda expressions. The implication of this research as a information to the public thata novel is not only use full as a reading at leisure or entertainment, but the novel can also be functioning as media of propaganda